The A Comparative Study of Idioms about Prohibition between Thailand and Laos People’s Democratic Republic - Buabme, Janejira (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
The objectives of this research intention to use prohibitive idioms between Thailand and Laos People’s Democratic Republic. A corpus of prohibitive idioms consisted of 100 Thai idioms published in Old Strategy: an Analysis of Thai Wisdom by Sanom Khrutmuang and 100 Lao idioms by Lao experts, and then the belief and intention of idiom use were compared. Intention to use prohibitive idioms between Thailand and Laos People’s Democratic Republic, there were three main aspects of use intention. 1) Eighty-seven pairs of intention similarities to use idioms. 2) Five pairs of intention differences to use idioms. 3) Eight pairs of intention having some similarities or differences.